Leaders guide for developing a Community Wildfire Protection Plan - Western Governors' Association, author (Colorado State University. Libraries, 2010)
This Leaders Guide is designed to supplement the document entitled: "Preparing a Community Wildfire Protection Plan: Handbook for Wildland-Urban Interface Communities."
Keywords: fire protection engineering; wildfires; fire prevention; fire safety; public safety; community sustainability; natural resources; fire protection districts; Healthy Forests Restoration Act